Особливості дослідження функціонального стану льотного складу в цілях лікарсько-льотної експертизи - Люлько, О.М. (Актуальні проблеми транспортної медицини, 2008)
В данной статье приводятся данные о состоянии здоровья летчиков при выполнении насыщенной полноценной программы летного обучения. Была изучена структура заболеваний среди летного состава. Ориентируясь на полученные данные, можно с уверенностью судить о влиянии регулярных полетов на организм летчиков. На основании показателей гемодинамики в прогностических целях отдается предпочтение использованию модифицированной пробы Вальсальвы вместо традиционного общепринятого теста с 20 при седаниями. Information about the state of health of pilots at implementation of the saturated valuable program of the flying teaching is presented in this article. The structure of diseases among flying composition was studied. Oriented on findings, it is possible with a confidence to judge about influence of regular flights on the organism of pilots. On the basis of indexes of gemodynamics in prognosis aims the preference gives oneself up to the use of the modified test Val’sal’vy in place of the traditional generally accepted test with a 20 squatting.